Programming Encryption Algorithms with Steganography - Gençoğlu, Muharrem Tuncay (Nişantaşı Üniversitesi, 2017)
In this paper a different cryptographic method is introduced by using Power series transform, science of steganography. Here,we produce a new algorithm for cryptology,we use Expanded Laplace transformation of the exponential function for encrypting the plain text and we use codes of ASCII for support to the confidentiality of the chipertext. After, Chipertext have embedded by steganographic method in another plaintext to hide the existence of chipertext. We show  corresponding inverse of Power Series transform for decryption. Then; Experimental results were obtained by writing a computer program for crypto machines.